(untitled) - Atlas, Ronald M. (Boca Raton, Fla., 2004)
Lists the formulations, methods of preparation, and uses for over four thousand microbiological media. With 30 percent more entries than the previous edition, the book includes new information on international collections of microorganisms and expanded information on yeast, algae, and archaea. It also contains formulations and uses of media for isolation, culture, identification, and maintenance of microorganisms.
Keywords: Microbiology,Culture media,Phương tiện truyền thông văn hóa,Vi sinh vật; Cultures and culture media